2011
DOI: 10.1021/cb2001796
|View full text |Cite
|
Sign up to set email alerts
|

Selective Targeting of Disease-Relevant Protein Binding Domains byO-Phosphorylated Natural Product Derivatives

Abstract: Phosphorylation-dependent protein binding domains are crucially important for intracellular signaling pathways and thus highly relevant targets in chemical biology. By screening of chemical libraries against 12 structurally diverse phosphorylation-dependent protein binding domains, we have identified fosfosal and dexamethasone-21-phosphate as selective inhibitors of two antitumor targets: the SH2 domain of the transcription factor STAT5b and the substrate-binding domain of the peptidyl-prolyl isomerase Pin1, r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
48
0
5

Year Published

2013
2013
2018
2018

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 32 publications
(54 citation statements)
references
References 38 publications
1
48
0
5
Order By: Relevance
“…We recently reported Fosfosal as a STAT5b SH2 domain inhibitor ( K i =17.4 μ m )[9] (Figure 1 a). Structure–activity relationships of Fosfosal revealed that deleting the carboxylic acid retained partial activity, but deleting the phosphate led to a complete loss of activity against STAT5b.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…We recently reported Fosfosal as a STAT5b SH2 domain inhibitor ( K i =17.4 μ m )[9] (Figure 1 a). Structure–activity relationships of Fosfosal revealed that deleting the carboxylic acid retained partial activity, but deleting the phosphate led to a complete loss of activity against STAT5b.…”
mentioning
confidence: 99%
“…a) Structures of Fosfosal[9] and 1. b) Activities of 1 against the SH2 domains of STAT family members and the tyrosine kinase Lck analyzed in binding assays based on fluorescence polarization. c) Binding of 1 to the STAT5b SH2 domain as predicted by docking with AutoDock Vina.…”
mentioning
confidence: 99%
“…The known structure (PDB: 3TC5) of dexamethasone 21-phosphate in complex with Pin1 was used as a guide for our designs. 22 Pin1 consists of two functional domains, one is an amino-terminal WW domain involved in protein-protein interaction, and the other one is a COOH-terminal PPIase domain which functions in catalysis. 2 Crystallographic analysis revealed that the catalytic center of PPIase domain composed of hydrophobic domain and basic cluster formed by Lys63, Arg68, and Arg69 residues.…”
mentioning
confidence: 99%
“…2 Crystallographic analysis revealed that the catalytic center of PPIase domain composed of hydrophobic domain and basic cluster formed by Lys63, Arg68, and Arg69 residues. 22 Considering that the general tetracyclic ring structure might produce a hydrophobic interaction with the shallow surface, we aim to enhance the compounds' interactions with the basic amino acid residues within the subpocket. It was expected that if a carboxyl group or acid bioisostere was introduced into it for interaction with the basic cluster in Pin1, its inhibitory effect would be enhanced.…”
mentioning
confidence: 99%
See 1 more Smart Citation